Mecanismos fisiológicos como efetores da variação individual na tolerância a fatores abióticos (temperatura e hipóxia) nos teleósteos de água doce pacu (Piaractus mesopotamicus) e tilápia-do-Nilo (Oreochromis niloticus) - Blasco, Felipe Rocco (2020)
The anthropic influence on the aquatic environment will be responsible for an increase in the frequency and intensity of exposure of fish to two very important stressors in the viability of these animals: temperature and hypoxia. Temperature is already well established as the main abiotic factor to influence the viability of ectothermic animals. Due of the efficient heat exchange that takes place between the branchial epithelium and the body surface with the surrounding environment and the relative low heat production by these animals, usually the ambient temperature will dictate the body temperature, which will inevitably influence the metabolic rate. Hypoxia has the characteristic of limiting the availability of oxygen (O2) for the performance of essential functions for the maintenance of life, as well as for the performance of activities that would ensure greater evolutionary success and fitness of the animals to the environment in which they live. Considering that both stressors are related to the availability and consumption of O2, the study of the three variables that comprise an individual's aerobic metabolic phenotype (standard metabolic rate - SMR; active metabolic rate – AMR and aerobic scope - AS) has proved to be an efficient tool in order to better understand the mechanisms related to individual variation in tolerance to such stressors. Using as experimental models two abundant species in the Brazilian ichthyofauna, Nile-tilapia (Oreochromis niloticus) and pacu (Piaractus mesopotamicus), we studied whether the premises mentioned are related to tolerance. In experiment 1 we developed a new protocol to test the acute heating tolerance (CTswim). Such test aims to be an ecologically more relevant alternative and whose factors associated with the tolerated thermal limit are well understood, different from the current CTmax test. For both studied species, CTswim was approximately 2ºC lower than CTmax. In addition, the fatigue presented during the heated swimming protocol proved to be an interesting “endpoint” since this behavior was preceded by the adoption of an anaerobic swimming profile. This fact leads us to believe in an inability to provide O2 to the tissues in operation, indicating that the viability of the animals is possibly compromised at temperatures lower than those reported by CTmax. In experiment 2, using pacu as an experimental species, we investigated the correlation between the individual metabolic phenotype and the tolerance to acute heating and hypoxia, in addition to trying to discover a possible cross-tolerance between both stressors. The tolerance to acute heating was measured using the protocols CTswim and CTmax and the tolerance to hypoxia was measured using the Scrit calculation, that is, the O2 saturation in the water in which the animal loses the ability to oxirregulate. We found that the tolerance to acute heating, in both protocols, was not dependent upon the metabolic phenotype of the individuals, as well as the tolerance to hypoxia was not dependent upon SMR. Regarding the cross tolerance between stressors, we found a correlation between tolerance to hypoxia and CTswim, in line with the founds from our previous study about the importance of O2 supply in this new thermal tolerance test. In experiment 3, we studied the hypothesis that states that individuals of greater mass are more susceptible to heating due to limitations in the ability to provide O2 for aerobic activities. With this aim we used individuals of Nile-tilapia that varied by more than one order of magnitude in body mass and exposed them to the CTmax and CTswim tests. We found that the AS calculated at the acclimatization temperature had no correlation with the animal's body mass, as well as for thermal tolerance at CTmax. However, the acute heating tolerance in the CTswim proved to be inversely proportional to the animal's mass, as well as the MMR calculated during the test. Such findings show us that when exposed to acute warming, bigger animals have their ability to swim impaired at lower temperatures than the conspecifics smaller ones. This character can come to hinder the survival and fitness of these individuals in a scenario where such situations may be more frequent.